2021
DOI: 10.1177/1087724x211047247
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Pass Deferred Maintenance Costs to the Next Generation! The Effects of Politics on State Highway Maintenance Spending

Abstract: Routine maintenance spending for public infrastructure is critical for reducing life-cycle costs, and improving asset preservation and quality. Yet, states focus more on building new roads and expansion than maintaining existing assets’ conditions. Deferred maintenance costs are transferred to the future taxpayers, and they will eventually pay the expensive price. So far, there is little academic endeavor to examine the determinants of state and local routine maintenance spending. This study uses a panel data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Given the delay before the consequences of infrastructure spending cuts are felt, infrastructure expenditure is particularly vulnerable during periods of fiscal austerity . This delay is in contrast to the effects on other budget lines, where a reduction in spending has an immediate adverse impact on livelihoods (Gupta, Liu, and Mulas Granados 2015;Kim 2022) .…”
Section: Fiscal Risks From Direct Government Provision Of Infrastructurementioning
confidence: 87%
“…Given the delay before the consequences of infrastructure spending cuts are felt, infrastructure expenditure is particularly vulnerable during periods of fiscal austerity . This delay is in contrast to the effects on other budget lines, where a reduction in spending has an immediate adverse impact on livelihoods (Gupta, Liu, and Mulas Granados 2015;Kim 2022) .…”
Section: Fiscal Risks From Direct Government Provision Of Infrastructurementioning
confidence: 87%
“…34 improved state highway quality by raising state highway maintenance expenditures, and the states using the modified approach had a larger effect on road maintenance spending compared to the states using depreciation accounting. Kim (2022) employs a panel data analysis covering 47 states from 1995 to 2009 to investigate the effects of politics on state highway routine maintenance spending. The author confirms that political election incentives and divided governments are the key factors delaying state highway routine maintenance spending.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Routine maintenance is vital to ensure the function and safety of infrastructure assets. Studies have shown that delayed maintenance results in faster deterioration of capital assets (e.g., Chen, 2017), causes travel delays (Bock & Blemings, 2024), increases traffic fatalities (Nguyen-Hoang & Yeung, 2014), and incurs greater costs of infrastructure rebuilding (e.g., Dornan, 2002;Kim, 2022). In practice, the maintenance of existing public infrastructure has often been neglected in favor of building new infrastructure in both developed and developing countries (Rioja, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation